Contemporary Sociological Theory and Its Classical Roots The Basics - Ritzer, George; Stepnisky, Jeffrey (New York The McGraw-Hill, 2013)
This text is an introductory text to sociology theory. It defines the nature of sociology theory, discusses some of the controversy surrounding the traditional definition of theory, analyses the alternate perspective and offers non-traditional (multicultural) examples.
Keywords: Sociology. Sociology -- History